Power and identity in the creative writing classroom : the Authority Project - Leahy, Anna, 1965- (New writing viewpoints, 2005)
Remaps theories and practices for teaching creative writing at university and college level. This collection critiques well-established approaches for teaching creative writing in all genres and builds a comprehensive pedagogy based on issues of authority, power, and identity.